“Comparación in vitro del efecto antibacteriano de los extractos etanólicos de Aloe vera (L) y Curcuma longa L. frente a Streptococcus mutans ATCC 25175” - Rios Vonderheyde, Sara Antonieta (2022)
The purpose of this experimental research "in vitro" was to compare the antibacterial effect of the ethanolic extract of Aloe vera (L) and Curcuma longa L., on the growth of Streptococcus mutans ATCC 25175. Ethanolic extracts of Aloe vera ( L) and Curcuma longa L. at concentrations of 25%, 50% and 75% each. The Streptococcus mutans strain ATCC 25175 was reactivated in brain heart broth. To evaluate the antibacterial effect, 10 repetitions of each concentration were carried out using the Kirby Bauer method, making use of filter paper disks placed in plates containing Müeller Hinton Agar-blood inoculated with S. mutans. Chlorhexidine 0.12% was used as a positive control and distilled water as a negative control. The diameters in (mm) of the inhibition halos around each disc were measured with a vernier pachymeter. The ethanolic extract of Curcuma longa L. did not present inhibition halos for the concentrations of 25% and 50%, but it did present an inhibition halo of 8.2 mm for the 75% concentration. The ethanolic extract of Aloe vera (L) presented an inhibition halo of 8.4 mm for the 25% concentration, 9.5 mm for the 50% concentration and 11.7 mm for the 75% concentration. Chlorhexidine 0.12% presented an inhibition halo of 25.2 mm while the negative control did not present an inhibition halo. The ANOVA test showed that there is a statistically significant difference between the concentrations of the extracts. When comparing the results of both extracts, it is concluded that the ethanolic extract Aloe vera (L) at 75% presented the greatest antibacterial effect against S. mutans.